2023
DOI: 10.1038/s41477-023-01354-8
|View full text |Cite
|
Sign up to set email alerts
|

Tight genetic linkage of genes causing hybrid necrosis and pollinator isolation between young species

Abstract: The mechanisms of reproductive isolation that cause phenotypic diversification and eventually speciation are a major topic of evolutionary research. Hybrid necrosis is a post-zygotic isolation mechanism in which cell death develops in the absence of pathogens. It is often due to the incompatibility between proteins from two parents. Here we describe a unique case of hybrid necrosis due to an incompatibility between loci on chromosomes 2 and 7 between two pollinator-isolated Petunia species. Typical immune resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Disturbed hormone signaling or function has also been implicated in cases of hybrid necrosis and another example of hybrid necrosis may be linked to selection for copper tolerance and may thus represent the consequence of adaptation to different environmental conditions (MacNair and Christie 1983 ). In another case, tight linkage was found between genes causing hybrid necrosis and major genes involved in the adaptation to different pollinators, again illustrating the effects of local environmental adaptation on genetic incompatibilities (Li et al 2023 ). Thus, depending on the divergence of the parental components of a cross, different phenomena act on the fitness of generated hybrids, which has consequences for the design and the organization of hybrid breeding programs.…”
Section: Heterosismentioning
confidence: 89%
“…Disturbed hormone signaling or function has also been implicated in cases of hybrid necrosis and another example of hybrid necrosis may be linked to selection for copper tolerance and may thus represent the consequence of adaptation to different environmental conditions (MacNair and Christie 1983 ). In another case, tight linkage was found between genes causing hybrid necrosis and major genes involved in the adaptation to different pollinators, again illustrating the effects of local environmental adaptation on genetic incompatibilities (Li et al 2023 ). Thus, depending on the divergence of the parental components of a cross, different phenomena act on the fitness of generated hybrids, which has consequences for the design and the organization of hybrid breeding programs.…”
Section: Heterosismentioning
confidence: 89%
“…These last two lineages, P. parodii and P. axillaris A2, could have given rise to the colored lineages in the clade as they advanced colonizing new environments. The albino P. parodii and P. axillaris A1 and the red-flowered P. exserta share several polymorphisms (e.g., Segatto et al, 2014 ; Li et al, 2023 ), despite currently not being found close. Mainly regarding P. exserta , this species inhabits a very particular microenvironment, inside small caves where plants grow protected from direct sunlight and rain ( Stehmann et al, 2009 ; Segatto et al , 2014 ), an inhospitable environment for other Petunia species.…”
Section: Discussionmentioning
confidence: 99%
“…The switch to hummingbird pollination in Petunia exserta involved major-effect alleles specifying red color, UV-absorbing pigments, lack of floral scent, and elongated reproductive organs that are clustered in a supergene-like region of low recombination (Hermann et al, 2013). This region also includes a locus involved in hybrid incompatibility with P. axillaris (Li et al, 2023), an arrangement that may help to maintain floral differences in sympatry. A similarly concentrated architecture is found in the M. lewisii -M. cardinalis system, where YUP is located in a region of suppressed recombination with loci affecting anthocyanin content, nectar production, and floral organ length, along with a hybrid lethality factor (Bradshaw et al, 1995(Bradshaw et al, , 1998Fishman et al, 2013).…”
Section: Reviewmentioning
confidence: 99%
“…This region also includes a locus involved in hybrid incompatibility with P . axillaris (Li et al ., 2023), an arrangement that may help to maintain floral differences in sympatry. A similarly concentrated architecture is found in the M .…”
Section: The Maintenance Of Polygenic Differences In Recently Diverge...mentioning
confidence: 99%